Brief repeated virtual nature contact for three weeks boosts university students' nature connectedness and psychological and physiological health during the COVID-19 pandemic: A pilot study - Lau, Sam S. S.; Leung, Sharron S. K.; Wong, Jonathan W. C.; Lee, Terence C. P.; Cartwright, Stephen R.; Wong, Janet T. C.; Man, Jackie; Cheung, Ethan; Choi, Regene P. W. (Frontiers in Public Health, 2023)
The COVID-19 pandemic and its associated uncertainties and restrictions have adverse impacts on university students' mental wellbeing. Evidence shows that virtual nature contact has mental health benefits. However, little is known about the potential beneficial health impacts of virtual nature contact during times of social distancing, when access to the natural environment is restricted. This pilot study aimed to examine the effectiveness of a 3-week virtual nature contact in improving nature connectedness and reducing psychophysiological stress. A sample of 56 university students in Hong Kong was randomly assigned to control and nature interventions using 2-D video played for 15 min three times a week for 3 weeks. Nature connectedness, perceived restorativeness and psycho-physiological wellbeing were measured. Our findings show significant changes in psychological stress levels after nature interventions compared with the baseline, including increased happiness and stronger emotions of comfort and relaxation. When compared with the control group, the results show the nature intervention group has significantly higher levels of nature connectedness, happiness, and positive affect, but no significant effects on other psychological and physiological variables (e.g., cardiovascular responses). Our preliminary findings highlight the potential use of virtual nature contacts in bolstering university students' wellbeing at times of pandemic or when in-person visit to the natural environment is not feasible.